2016
DOI: 10.5415/apallergy.2016.6.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Imidacloprid inhibits IgE-mediated RBL-2H3 cell degranulation and passive cutaneous anaphylaxis

Abstract: BackgroundImidacloprid has been commonly used as a pesticide for crop protection and acts as nicotinic acetylcholine receptor agonists. Little information about the relationship between imidacloprid and allergy is available.ObjectiveThis study aims to examine the effects of imidacoprid on IgE-mediated mast cell activation.MethodsThe rat basophilic leukemia cell line RBL-2H3 (RBL-2H3 cells) were treated with 10-3 – 10-12 mol/L imidacloprid, followed by measuring the mediator production, influx of Ca2+ in IgE-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The increased intracellular calcium constitutes calcium-calmodulin complex that leads to the exocytosis of granules by inducing the SNARE complex activation [53, 74, 75]. Consistent with previously reported studies, we found that stimulation of IgE/Ag increases the levels of intracellular calcium in RBL-2H3 cells (Figure 4) [40, 41]. We observed that PBR-BuOH inhibited calcium influx assay compared with that in IgE/Ag-stimulated RBL-2H3 cells (Figure 4).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The increased intracellular calcium constitutes calcium-calmodulin complex that leads to the exocytosis of granules by inducing the SNARE complex activation [53, 74, 75]. Consistent with previously reported studies, we found that stimulation of IgE/Ag increases the levels of intracellular calcium in RBL-2H3 cells (Figure 4) [40, 41]. We observed that PBR-BuOH inhibited calcium influx assay compared with that in IgE/Ag-stimulated RBL-2H3 cells (Figure 4).…”
Section: Discussionsupporting
confidence: 90%
“…IgE-mediated degranulation requires increased calcium mobilization [40, 41]. To evaluate whether PBR-BuOH affects the calcium influx induced by IgE/antigen, RBL-2H3 cells were stained with calcium-sensitive dye Fluo-4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies on plasma histamine have shown that imidacloprid, a class of NN, inhibits IgE-mediated degranulation in rat mast cell model cells (RBL-2H3), mouse bone marrow-derived mast cells, and human basophilic cells (KU812). This inhibition of degranulation has been associated with α7 nAChR [ 20 , 21 , 22 ]. Therefore, in the present study, CLO exposure may have inhibited mast cell degranulation via α7 nAChR, thereby suppressing histamine secretion and the induction of inflammation.…”
mentioning
confidence: 99%